2018
DOI: 10.1049/iet-map.2018.5400
|View full text |Cite
|
Sign up to set email alerts
|

Tunable wideband frequency and switching polarisation reconfiguration antenna for wireless applications

Abstract: In this article, a circular microstrip tunable wideband frequency and polarisation reconfigurable antenna are investigated. The wideband tunability is achieved by placing the four varactor diodes between circular microstrip patch and circular ring. The impedance bandwidth of 2.09–2.96 GHz (34.52%) is realised by tuning the capacitance value from 4.15 pF (0 V) to 0.94 pF (6 V). Both frequency tunability and polarisation reconfigurability are controlled in the antenna using the proposed cascaded branch line coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…To reduce the effect of coupling between the main arm and supporting arms, a fixed capacitor is integrated into the antenna. To make the antenna as a frequency tuneable PIFA, the varactor diodes are used [24]. A 10 kΩ resistor is used in the LB and HB regions to bias the varactor diodes at the point P 1 and P 2 .…”
Section: Antenna Designmentioning
confidence: 99%
“…To reduce the effect of coupling between the main arm and supporting arms, a fixed capacitor is integrated into the antenna. To make the antenna as a frequency tuneable PIFA, the varactor diodes are used [24]. A 10 kΩ resistor is used in the LB and HB regions to bias the varactor diodes at the point P 1 and P 2 .…”
Section: Antenna Designmentioning
confidence: 99%
“…A search of published techniques for tuning compact and electrically small antennas in general terms revealed that tuneability is predominantly viewed in terms of tuneable input response (impedance matching from S 11 ). Of the sample of papers describing tuning techniques referenced [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], all either reported explicit tuning ranges in percentage terms with respect to a required S 11 threshold or provided the data required to do so. The aforementioned list gives a sample set of 18 papers, of which 15 were published in the last five years, thus the sample set is taken to be representative of contemporary reporting.…”
Section: Review Of Research In Tuneability and Transmission Performanmentioning
confidence: 99%
“…The trend for an increasing number of frequencies to be supported in one device has been showcased by the evolution of cellular communications, with the 9 bands specified for GSM [1] expanding to more than 50 to date in the present LTE-A specifications [2]. Other frequencyreconfigurable applications include public safety [3], cognitive radio [4], WLAN [5] and antennas combining multiple functions (e.g. [6] combining low-power WAN, GPS and Bluetooth).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some polarization reconfigurable antennas that only work in LP mode or CP mode have been proposed in References . In References , linear polarization reconfigurable antenna has been proposed. They are the antennas with several switchable LP modes, with a relatively narrow impedance bandwidth.…”
Section: Introductionmentioning
confidence: 99%